Moving Forward in African Economic History: Bridging the Gap Between Methods and Sources - Morten Jerven; Gareth Austin; Erik Green; Chibuike Uche; Ewout Frankema; Johan Fourie; Joseph Inikori; Alexander Moradi; Ellen Hillbom (African Economic History Network (AEHN), 2012)
The field of African economic history is in resurgence. This paper reviews recent and on-going research contributions and notes strengths in their wide methodological, conceptual and topical variety. In these strengths there is also a challenge: different methodological approaches may also result in divisions, particularly on the quantitative versus qualitative axis. The African Economic History Network has recently been formed to bridge the gap between methods and sources and to facilitate intellectual exchanges among the widest possible range of scholars working on Sub-Saharan economic history. This paper outlines current research projects and calls for future research as well as suggesting promising lines of enquiry in the discipline.
Keywords: N17; N27; N37; N47; N57; N67; N77; N87; N97; 330; Africa; Economic History; Sources; Methods; GDP; population; agriculture